Applying interactive multimedia Instructional System Design (ISD) in a language proficiency course: a look into learners learning styles / Aini Faridah Azizul Hassan, Othman Ismail and Nor Fazlin - Azizul Hassan, Aini Faridah; Ismail, Othman; ,, Nor Fazlin (Research Innovation Business Unit, 2014)
Today, there are countless study materials available in the market. Nevertheless, not all the materials are suitable to the students’ need in terms of learning contents, material presentation and learning styles. However, with properly customized learning materials, educators will be able to provide their students with better learning activities and more personalized learning opportunities. In this study, a customized and personalized learning courseware, designed based on the Felder& Silverman Learning Style Model (FSLSM), is proposed as a probable learning solution most appropriate and feasible for technology-based or self-learning environment. It characterizes students’ in four dimensions according to their preference in processing, perceiving, getting and understanding of information. Firstly, active/reflective dimension, this dimension categorizes students according to how they process information. Active students are categorized as retaining and understanding information better by doing something with the learned material such as they like to discuss, apply or explain it to their peers. By contrast, reflective students tend to think about the concepts quietly first and they prefer to work alone. Next, sensing/intuitive dimension, students in this group are distinguished based on their understanding of the learning materials. As for sensing students, they like to learn facts and study concrete learning materials, whereas intuitive students are more comfortable with abstract materials. Moreover, in order to learn from concrete material sensing students prefer to solve problems using standard approaches and dislike complicated problems. They learn best when they see how it connects to the real world and they tend to be more practical. Intuitive students like discovering possibilities and relationships. Moreover, students in this category tend to be more innovative and like challenges than sensing students. Thirdly, visual/verbal dimension students differentiate in the way they get the information. Normally, visual students when they see pictures, diagrams and movies make them remember best. Their strategy to remember better is using techniques such as highlighting to colour-code their notes. In comparison, verbal students learn best from written and spoken explanations. Lastly, sequential or global dimensions, whereby sequential students prefer to learn in a linear way and they tend to follow logical steps in order to find solutions. They are also interested in the details. By contrast, global students prefer to look at learning materials randomly. They can put things together once the see the ‘big picture’. They are interested in overviews and will look for connections between different areas. The purpose of using this solution is to cater the different students’ learning styles. A research question was asked on what learning style(s) is/are preferred by the full-time (FT) and distance learners (ePJJ). An online Index of Learning Styles (ILS) questionnaire was employed as a measuring instrument. A total of 55 students from two classes, FT and ePJJ at UiTM Shah Alam participated in the study during the Sept-Dec 2013 session. The findings reveal that majority are inclined to active, sensing, visual and sequential students. The implication on this study supports the notion that students’ learning styles can affect their success in language learning. Hence, language lecturers/instructors, who address their students’ learning style, can provide their students with a more effective learning environment.